Psychometric Properties of the 14 Items Oral Health Impact Profile Questionnaire Translated into the Macedonian language - Nikolina Kenig; Kalina Sotiroska Ivanoska; Julijana Nikolovska (Acta Stomatologica Croatica, 2023)
Objective: Due to the consideration that oral/dental health is an important part of general health, well-being, and an individual’s quality of life, the need for appropriate instruments assessing oral health-related quality of life is emphasized. This study aimed to evaluate the psychometric properties of the Oral health-related quality of life questionnaire consisting of 14 questions among the Macedonian language-speaking adults (OHIP-MAC 14). Material and methods: A total of 270 adults participated in the study. The reliability of the questionnaire was examined by testing the internal consistency and reproducibility (test-retest). The responsiveness of the instrument was tested by computing the pre-intervention and post-intervention OHIP-14 scores using the paired t-test followed by the determination of the effect-size. The two aspects of the construct validity were evaluated: concurrent validity and discriminative validity. Results: A concurrent validity analysis confirmed that the instrument performed well. Discriminative validity also confirmed good psychometric properties (P<0.01). The ICC statistics and the Cronbach alpha coefficients indicated the appropriate reliability of the instrument for the included groups of participants. The responsiveness of the questionnaire was also acceptable (P<0.01) demonstrating the large effect-size of 1.43. Conclusion: The OHIP 14 MAC showed acceptable psychometric properties and can be recommended as a valuable instrument in assessments of the Oral health-related quality of life in the Republic of North Macedonia.